The influence of perceived organizational climate on retention intention among faculty in private colleges in Yunnan, China: The mediating role of decent work - Chen, Hangsheng; Wang, Hsuan-Po (Edelweiss Applied Science and Technology, 2025)
Retaining faculty members has become a top priority for private colleges in China. This study, grounded in Social Exchange Theory, investigates the effect of perceived organizational climate (OC) on faculty members’ intention to stay (ITS) and examines the mediating role of decent work (DW) in this link. Faculty members from four private colleges in Yunnan Province, China, participated in a structured questionnaire survey. Of the 782 distributed questionnaires, 114 were excluded for not meeting the research criteria, resulting in 668 valid responses. The findings suggest that perceived OC has a significant positive influence on faculty members’ ITS. OC has a significant positive influence on DW. Additionally, DW also has a significant positive influence on ITS. Moreover, DW partially mediates the link between OC and ITS.